Propriedades tecnológicas da madeira termorretificada de três espécies de Eucalyptus - Cademartori, Pedro Henrique Gonzalez de (2012)
This study aimed to evaluate physicomechanical and chemical behaviour of Eucalyptus grandis, Eucalyptus saligna e Eucalyptus cloeziana thermally modified wood. To achieve this, six trees of each species were randomly selected and samples measuring 1.6 x 1.6 x 25cm were prepared. The samples were thermally modified through exposure to nine treatments in an oven and in an autoclave steriliser. The process conditions in the oven were: temperatures between 180 and 240ºC and time of exposure of 4h, whereas for the treatments in autoclave a constant temperature (127°C) and pressure (1.5kgf/cm²) were used for 1h. The evaluation of the physical properties was done through the performance of weight loss, equilibrium moisture content, stability dimensional and specific gravity tests. Colour changes and wettability were measured by colorimetric and contact angle techniques, respectively. Regarding mechanical properties, thermally modified wood was evaluated through the performance of static bending tests and non-destructive ultrasonic tests. Chemical modifications were qualitatively measured through infrared spectroscopy (ATR-IR). The main results showed that thermal treatments significantly influenced weight loss, equilibrium moisture content and dimensional stability. On the other hand, specific gravity did not show a great behaviour in order to explain the influence of thermal treatments on wood. A gradual darkening in both radial and tangential sections was observed, mainly due to a high reduction of L* after treatment 2 (180°C), since a* and b* showed distinct behaviour. Generally, stiffness remained constant when related to the control treatment, whereas mechanical strength decreased significantly, mainly after the treatments 6, 7, 8 and 9. The use of the non-destructive ultrasound technique obtained coefficients of determination between 0.66 and 0.80 for the relationship MOE x Ed. The wettability of thermally modified wood presented the best results in the treatments 2, 3, 4 and 5 for all the species, with the contact angle increasing and remaining with high stability as a function of time of exposure. Infrared spectroscopy showed modifications in different peaks, mainly related to the hemicelluloses and crystallinity of the structure, representing thermal degradation of the material as a function of temperature of treatment. Therefore, the thermal treatments reduced hygroscopicity and modified the colour of the wood. The mechanical strength was reduced significantly and the ultrasound was efficient in order to estimate the modulus of elasticity. Wettability decreased significantly as a function of the thermal treatments and infrared spectroscopy (ATR-IR) demonstrated to be an excellent tool for the qualitative analysis of chemical modifications due to thermal treatments.